Oral Candida spp. colonization in human immunodeficiency virus-infected individuals - Moris, D. V. [UNESP]; Melhem, M. S. C.; Martins, M. A.; Mendes, R. P. [UNESP] (Bmc, 2008)
Several yeast species of Candida genus can colonize the skin as well as the mucous membrane of the vagina and the digestive tract for short or long periods. Depending on the host's immunological state and the yeast's virulence, colonization can become an infection, invading the colonized tissues and also disseminating. AIDS is characterized by the host's intensive and progressive immunodepression which manifests as diverse symptoms, mainly lesions in the mouth. Oral candidiasis is the most prevalent opportunistic infection in individuals infected with human immunodeficiency virus (HIV) and is an important indicator of the disease progress and the immunosuppression increase. The factors involved in the equilibrium between Candida spp. and HIV-infected subjects are sometimes contradictory and were evaluated in the present study specially for colonization.
Keywords: Candida spp.; colonization; human immunodeficiency virus-infected individuals